Towards a Personalized mHealth Model Using Intelligent Conversational Agents - Vaz, Noeli Antonia Pimentel; Silva, Kairo A. Lopes da; Velasco, Gislainy; Mata, Luciana Regina F. da; Fernandes, Deborah S. Alves; Carvalho, Sergio T. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
Mobile health (mHealth) applications are increasingly used for health monitoring but often struggle to engage users effectively. This study proposes a computational model to personalize mHealth experiences using intelligent conversational agents that combine Large Language Models (LLMs), vector-based knowledge retrieval, and sentiment analysis. An experiment was conducted to evaluate the model’s application in assisting patients with urinary incontinence after radical prostatectomy. The results demonstrated that incorporating a specialized knowledge base significantly improves the personalization of clinical support. The study underscores the potential of LLMs to improve user experience in healthcare applications and highlights the need for further refinements in adapting interaction strategies to better meet patient needs.